MENGGALI DASAR MATEMATIKA: META-ANALISIS PENGENALAN KONSEP MATEMATIKA PADA ANAK USIA DINI UNTUK PEMBELAJARAN YANG LEBIH EFEKTIF - Jayadi, Usman (Berajah Journal, 2024)
The introduction of mathematical concepts in early childhood has a significant impact on cognitive development and academic abilities. This article presents a meta-analysis of 15 studies exploring effective teaching methods for preschool mathematics. The analysis highlights the most effective approaches to introducing basic mathematical concepts, including play-based learning, visual aids, technology integration, and social interaction. Findings show that play-based learning and collaborative approaches significantly enhance children's engagement and understanding, with effect sizes of 0.75 and 0.74, respectively. Visual aids were also proven effective, with an effect size of 0.85, while educational technology, through interactive applications, achieved an effect size of 0.82. Emphasizing enjoyable and interactive learning can build a positive view of mathematics and improve children’s ability to apply concepts in real-world contexts. This analysis provides educators and parents with guidance for designing more effective learning experiences, supporting a strong mastery of mathematical concepts in early childhood.